Biosurfactant: A Next-Generation Tool for Sustainable Remediation of Organic Pollutants - Sharma, Neha; Lavania, Meeta; Lal, Banwari (Frontiers in Microbiology, 2022)
Petroleum hydrocarbons are energy resources that majorly contribute pollutants to the environment. These pollutants may cause serious health issues, and hence, for the regulation of these contaminants, the development of sustainable alternative technologies has been considered, without causing further harm to the environment. One such alternative is biosurfactants (having low toxicity and being biodegradable) produced by numerous microbial species that have a tendency to remediate organic pollutants. Biosurfactants are amphiphilic compounds that are categorized into two types based on their molecular mass. Biosurfactants can be generated extracellularly or as a part of the cell membrane of microorganisms (bacteria, fungi, and algae). This review provides a detailed view of the types of biosurfactants, their properties, and the mechanism involved in the degradation of oil spills.